2020
DOI: 10.29333/iji.2020.13119a
|View full text |Cite
|
Sign up to set email alerts
|

Using Android Media for Chemistry Learning Construction of Motivation and Metacognition Ability

Abstract: The 21st century and industry revolution 4.0 has been technology used part of life. This research intended to understand the effect of android application for chemistry learning (reaction rate material) to construction of motivation and metacognition of high school students. Research aimed to determine the worthiness and effectiveness of chemistry learning using android with Research and Development (R&D) method of 4D by Thiagarajan and experiment method. The instruments used in this research consist of expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The Android Applications used in the study were Chemi Lab-Interactive Chemistry Learning (Davenport et al, 2012), High School Chemistry Class (Astiningsih & Partana, 2020), Periodic Table-Game (Setu & Basar, 2019), MEL VR Science Simulations (Sharpe et al, 2008) and Elements and Periodic Table Quiz (Naik, 2017). These applications were used as the student's learning material in Science.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Android Applications used in the study were Chemi Lab-Interactive Chemistry Learning (Davenport et al, 2012), High School Chemistry Class (Astiningsih & Partana, 2020), Periodic Table-Game (Setu & Basar, 2019), MEL VR Science Simulations (Sharpe et al, 2008) and Elements and Periodic Table Quiz (Naik, 2017). These applications were used as the student's learning material in Science.…”
Section: Methodsmentioning
confidence: 99%
“…The Android Application used in the study, namely; Chemi Lab-Interactive Chemistry Learning (Davenport et al, 2012), is a 3D interactive application for learning fundamental Chemistry concepts. Elements & Periodic Table Quiz (Setu & Basar, 2019) this application, students can learn the names and symbols of all 118 chemical elements of the Periodic Table (Astiningsih & Partana, 2020) with this application. IN MEL VR Science Simulations (Sharpe et al, 2008), students can explore chemical elements, atoms and molecules in Virtual Reality (Naik, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Farida, Jumadi, Wilujeng, and Senam (2018) reported the development of Android as an effective medium for teaching in Indonesia, using global warming as a topic, to improve the scientific literacy of junior high school students. Utilizing Android-based learning is currently trending as the application of learning of the 21st century (Calimag, Mugel, Conde, & Aquino, 2014;Liliarti & Kuswanto, 2018;Astiningsih & Partana, 2020). In a survey study of 605 people in three major cities in Indonesia, Puspitasari and Ishii (2016) reported that young people with high levels of education tend to use cellular International Journal of Instruction, April 2021 • Vol.14, No.2 Internet on their smartphones.…”
Section: Introductionmentioning
confidence: 99%
“…In the Indonesian national curriculum (K-13) it is stated that teachers should be able to create more innovative and creative in conducting the teaching-learning activities, so the goals of national education can be achieved [2]. The application of learning media on technology-based is one way the teachers could be done in the learning process [3][4]. So, by using learning media on technology-based, students are expected to be more involved and enthusiastic in the learning process.…”
Section: Introductionmentioning
confidence: 99%